I KETOET GEDE DAN LUKISAN WAYANG KACA NAGASEPAHA: Analisa Genetika Visual Lukisan Bali Utara - Purwita, Dewa Gede (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Visual genetics in this case I use to provide a kind of term frame to analyze the forms of form that affect an artist or artist in presenting his work. As in the case of the painting I Ketoet Gede who apparently absorbed the visual of classical Balinese painting which in this case is Kamasan Village, Klungkung as a source that is still alive today. I ketoet gede then on the initiation of van der tuuk able to present things that break the principles of classical art of Bali. After the big ketoet, more or less half a century later appeared Jro Dalang Diah who started the birth of glass painting in Nagasepaha Village which then inherited the visual genetics typical of North Bali.